Teachers' and Students' Attitudes towards the Integration of YouTube Videos in EFL Classroom to Promote Autonomous Learning. The Case of First Year Master Students at Souk-Ahras University - Ilhem ARAIBIA (My University, 2022)
Abstract Technology has impacted almost every aspect of life today, and education is no exception. Autonomy has always been one of the very complex tasks in the foreign language learning (FLL) process. Consequently, students have many troubles to improve their autonomy. Therefore, the current study is meant to explore the importance of integrating YouTube videos to promote autonomous learning of first year master students of English at Souk Ahras University. It aims at investigating the extent to which the integration of YouTube videos can promote EFL learners' Autonomous learning, and examine teachers' and students' attitudes of using YouTube videos to promote autonomous learning. It is hypothesized in this research that both teachers and learners have positive attitudes towards integrating YouTube Application to promote learners' autonomy. To achieve the objective of this study, we relied on a descriptive method that focuses on quantitative and qualitative framework. To this end, a questionnaire and an interview were administered to first-year master students and to teachers from the department of English respectively. According to the findings of this investigation, the claimed hypothesis is confirmed.